IMPACT OF DIFFERENT FACTORS ON VOLUME PROPERTIES OF HUMAN HEMOGLOBIN (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Impact of different factors (temperature, group separation, concentration) on volume properties of human hemoglobin (HHb) has been studied using densitometry method. Investigations were provided at temperatures 301.15, 309.75 and 313.15 K. It has been shown, that the densities, apparent partial specific volumes and partial specific volumes of HHb are different for separated and non-separated forms of HHb molecule.
Keywords: human hemoglobin, densitometry, apparent partial specific volume, partial specific volume, density